Group decision making in health care: A case study of multidisciplinary meetings. (10th June 2016) - Sharma, Vishakha; Stranieri, Andrew; Burstein, Frada; Warren, Jim; Daly, Sharon; Patterson, Louise; Yearwood, John; Wolff, Alan
Abstract: Recent studies have demonstrated that Multi-Disciplinary Meetings (MDM) practiced in some medical contexts can contribute to positive health care outcomes. The group reasoning and decision-making in MDMs has been found to be most effective when deliberations revolve around the patient's needs, comprehensive information is available during the meeting, core members attend and the MDM is effectively facilitated. This article presents a case study of the MDMs in cancer care in a region of Australia. The case study draws on a group reasoning model called the Reasoning Community model to analyse MDM deliberations to illustrate that many factors are important to support group reasoning, not solely the provision of pertinent information. The case study has implications for the use of data analytics in any group reasoning context.